THE USE OF ASSISTIVE TECHNOLOGY IN RESOURCE ROOMS FOR STUDENTS WITH DISABILITIES: POSSIBILITIES AND LIMITS - Gomes, Cláudia Maria Tavares; Coutinho, Diogenes José Gusmão (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2023)
This article starts from the conceptions of education that contemplates the real needs of students with disabilities, and analysis of the practices of teachers of the Multifunctional Resource Room of the municipal school network. Hence, a review in the literature is presented, pointing out the main currents of traditional thought to current trends in education. Allied to these studies, concepts and results of research on assistive technology are pointed out. And, finally, challenges are raised that have been overcome or to be achieved by Special Education teachers in an attempt to bring greater autonomy to students with intellectual disabilities.